Flow Control, Active and Passive Applications - Bergadà, Josep Maria; Bugeda Castelltort, Gabriel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint covers some recent advances in active and passive flow control applications. The reader should consider that the present reprint aims to simply introduce some of the many existing flow control applications. In fact, the goal of the editors is to open a door to this rather novel technology and highlight the importance of optimization techniques in AFC applications.